Frequency and Morphological Patterns of Malignant Intra Orbital Tumors in Various age Groups - , Mohammad Anwar, Tahira Soomro, Shahnaz Imdad Kehar (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the frequency and morphologic types of intraorbital tumors. Material and Methods: A retrospective study conducted at the department of pathology Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi. All intraorbital lesions received over a period of 5 years i.e. from Jan 2005 to Dec 2009 were reviewed. All specimens were formalin fixed, routinely processed for paraffin embedding, sectioned and finally stained with haematoxylin and eosin using standard procedures, when required special stains were performed. Results: During study period total of 360 cases of intra orbital lesions were received. Out of, which 115 (31.9%) were non-neo plastic and 245 (68.0%) were neo plastic lesions. Retinoblastoma and squamous cell carcinoma were the most common malignant intraocular and intraorbital tumor with mean age of presentation 4 years and 55 years respectively. Remaining cases include 16 cases of intraepithelial dysplasia, 10 cases of rhabdomyosarcoma, 6 cases each of sebaceous carcinoma and malignant lymphoma, 4 cases each of malignant melanoma, malignant fibrous histiocytoma and adenoid cystic carcinoma, 3 cases of optic glioma and 1 case of mucoepidermoid carcinoma. Conclusion: A variety of tumors can involve the orbit. The incidence of neoplastic lesion exceeded that of non-neoplastic lesion. The data will be help full for ophthalmologist, pathologist and epidemiologist for comparison with other studies.